Penyuluhan Pemanfaatan Hasil Hutan Bukan Kayu (HHBK) di Desa Kokotu, Kecamatan Bacan Barat, Kabupaten Halmahera Selatan - Irmayanti, Laswi; Ashari, Reyna; Nurdin, Aqshan Shadikin; Salatalohy, Asiah; Nurhikmah; Tamrin, Mahdi; Fatrawana, Adesna; Kamaluddin , Abdul Kadir (Jurnal Pengabdian Masyarakat Hutan, 2025)
Non Timber Forest Products (NTFPs) are biological forest products, both plant and animal and their derivatives originating from forests except wood. NTFPs play an important role for the community, for example, they can increase household income and improve the local economy, as done by the people of Kokotu Village, West Bacan District, South Halmahera Regency. Several types of NTFPs utilized by the people of Kokotu Village are rattan and bamboo for craft materials and various types of herbs for food and raw materials for traditional medicine. The opportunities for utilizing NTFPs in Kokotu Village are very large considering the condition of the forest which is still well maintained. Therefore, insights regarding the utilization of other types of NTFPs and their marketing need to be shared with the people of Kokotu Village. The purpose of implementing this NTFP utilization outreach activity is to provide the community with an overview of the types of NTFPs in their village and the opportunities for their utilization. The NTFP utilization outreach in Kokotu Village was carried out with the target of housewives went fluently, and the participants were quite enthusiastic about discussing the types of NTFPs in Kokotu Village. In addition, the materials presented were able to provide new insights regarding the potential and utilization of HHBK to the extension participants. Keywords: Counseling, Kokotu Village, NTFPs